Opportunities for an Interdisciplinary Integrated Approach to Improving the Culture of Environmental Safety (Eurasian Scientific Herald, 2022)
This article discusses environmental problems and solutions. The work also addresses the issues of environmental culture and education of schoolchildren and how important it is for the future of our planet.